Dealing with shares on a shareholder's death: the plight of the deceased's personal representative - Halim, Akmal Hidayah; Mohd Salim, Wan Noraini; Hassan, Halyani; Mohd Noor , Nor Azlina; Arshad, Azhani (2014)
Where a shareholder of a company dies, the right to his interest in the shares will pass to his estate beneficiaries. Nevertheless, before such process could take place, the shares would legally vest in the deceased shareholder’s personal representative via transmission of shares. Undeniably, the most serious impact affecting the estate beneficiaries is the fall in the current value of the shares between the death of the shareholder and the receipt by the estate beneficiaries. Hence, the personal representative is highly required to act expeditiously in order to minimize any loss in share value. This paper aims to examine the extent of the personal representative‘s duties in dealing with the shares prior to the estate distribution. This paper also seeks to analyze the liabilities of the personal representative together with the available options to the estate beneficiaries with regards to their entitlements to the shares. The study adopts the doctrinal analysis by examining the existing primary and secondary materials including statutory provisions as provided by the Probate and Administration Act 1959 and the Companies Act 1965, case law and other legal and non-legal literatures relating to the duties and liabilities of the personal representative in dealing with the deceased’s shares. It is found that the estate beneficiaries’ rights to the shares are restricted and subject to the Memorandum and Articles of Association of each company. As for the personal representative, he stands vulnerable to be sued for civil liability for the loss arising from his failure to promptly realize and convert the shares, or charged for criminal offences in cases where he wastes or converts the shares to his own personal use.